Dartfish – predstavitev kompleksnega in zmogljivega programskega orodja za kvalitativno analizo športnega nastopa - Vučković, Goran (Šport (Ljubljana), 2021)
Over the past decade, sports analytics has developed tremendously. This is due to the increasing need for detailed analyses and, consequently, the findings about sports performance which coaches and athletes use for appropriate planning and implementing of the training process from all aspects of the competitive or result-oriented development. Moreover, the development of analytics is strongly influenced by the growth and particularly capacity of the information technology which is indispensable for a thorough analytical approach. There are numerous different computer-software tools available on the market which can be used for performance analysis in sport in different ways. Computer programs differ in terms of complexity and thus also ability to perform simple or very complex and advanced analyses. One such complex and highly capable solution is presented in the article, namely the Dartfish 10 Pro S computer program.
Keywords: Dartfish; IKT; kvalitativna analiza; quantitative analysis; sodobna tehnologija; sport; sport analytics; šport; športna analitika; technology